2009
DOI: 10.1177/1059601108329377
|View full text |Cite
|
Sign up to set email alerts
|

Individual-Level Predictors of Task-Related Teamwork Processes

Abstract: This study investigates expertise (i.e., high level of individual task performance) and self-efficacy as predictors of an individual's contribution to teamwork processes (problem analysis, goal specification) during team meetings. Multilevel, multisource data from a longitudinal field study in 22 professional software design teams reveal large within-team variability in individual contributions to teamwork processes. Expertise positively predicted a team member's contribution to meeting processes 1 year later,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…In contrast, interviewers who are less efficacious may have difficulty making decisions about applicants. Other research has found that people who are highly efficacious are less likely to seek information from others, tend to consider fewer alternatives, and take less time to make decisions than people who are less efficacious (e.g., Sonnentag & Volmer, 2009;Stone, 1994). Cognitive load theory may help to explain these effects.…”
Section: Interviewer Individual Differencesmentioning
confidence: 99%
“…In contrast, interviewers who are less efficacious may have difficulty making decisions about applicants. Other research has found that people who are highly efficacious are less likely to seek information from others, tend to consider fewer alternatives, and take less time to make decisions than people who are less efficacious (e.g., Sonnentag & Volmer, 2009;Stone, 1994). Cognitive load theory may help to explain these effects.…”
Section: Interviewer Individual Differencesmentioning
confidence: 99%
“…The finding that procedural behaviors can actively promote proactive behavior thus offers promising opportunities for creating more efficient meeting processes and outcomes. Meetings research should continue to explore procedural communication as a tool for promoting good team meeting practices and thus facilitating team performance (Baran, Shanock, Rogelberg, & Scott, 2012;Kauffeld & Lehmann-Willenbrock, 2012;Sonnentag & Volmer, 2009). Furthermore, procedural communication significantly inhibited dysfunctional meeting behaviors within the team interaction process.…”
Section: Implications For Meetings Researchmentioning
confidence: 99%
“…For example, the person controlling the keyboard dominated cross-site communication even though the audio facility made contributions from any team member perfectly audible at either site. Sonnentag and Volmer (2009) studied how individuals in software design teams contributed to teamwork processes during team meetings. They found expertise to be a strong predictor of individuals' contributions.…”
Section: Meetings In Generalmentioning
confidence: 99%